KeV-region analysis of the neutron capture cross-section of 237Np. Issue 1 (2nd January 2022) - Rovira, Gerard; Katabuchi, Tatsuya; Tosaka, Kenichi; Matsuura, Shota; Kodama, Yu; Nakano, H.; Iwamoto, Osamu; Kimura, Atsushi; Nakamura, Shoji; Iwamoto, Nobuyuki
ABSTRACT: Neutron capture cross-section measurements for 237 Np have been conducted with the Accurate Neutron Nucleus Reaction Measurement Instrument (ANNRI) at the Materials and Life Science Facility (MLF) of the Japan Proton Accelerator Research Complex (J-PARC) using neutrons with energy ranging from thermal energy to 1 MeV. A time-of-flight (TOF) method using a NaI(Tl) detector was employed and the data were analyzed based on the pulse-height weighting technique in order to derive the neutron capture cross-section. The absolute capture cross-section was determined using the first resonance from JENDL-4.0 together with the total neutron flux derived from a 197 Au sample measurement in which the first resonance was completely saturated. Both normalization techniques present agreement within 1 % . The present results are also compared evaluated data libraries. There is a discrepancy of 10–25 % discrepancy from 0.5 to 20 keV with JENDL-4.0. Nonetheless, above this energy JENDL-4.0 seems to reproduce the present data better as the results agree within uncertainties up to 500 keV. The cross-section results contain uncertainties below 4 % from 0.5 to 30 keV. However, the total uncertainty increases to over 8 % above 30 keV. Along with the cross-section measurement, theoretical calculations with the CCONE code were performed to reproduce the present results.